ANALYSIS OF INFLUENCE OF HR, INCENTIVES AND SUPPORTING FACILITIES ACCRUAL BASED SAP IMPLEMENTATION OF THE GOVERNMENT NORTH SUMATERA PROVINCE - Ramadhan, Puja Rizqy (Accounting and Business Journal, 2019)
This study aims to analyze the effect of HR, Incentives and Supporting Facilities on accrual-based SAP implementation in the Provincial Government of North Sumatra. The type of research used is associative research / relationships. The population in this study amounted to 34 Regional Work Units in the Government of North Sumatra Province and the research sample numbered 102 which included the Financial Administration Officer, the Treasurer of Expenditure, and the Finance Staff. The data source of this research is primary data using a research instrument in the form of a questionnaire. The data collection method used is survey research. This study uses multiple linear regression analysis for statistical analysis and the regression model has been tested beforehand in the classical assumption test. The results showed that partially testing HR had a significant positive effect on the accrual-based SAP implementation, incentives have a significant positive effect on accrual-based SAP implementation, and supporting facilities have a significant negative effect on accrual-based SAP implementation. Simultaneous testing shows that HR, incentives, and supporting facilities significantly influence the accrual-based SAP implementation